An Analysis of Implicature in SMP Negeri 4 Soromandi - Irawati, Ika; Sulastri, Sulastri; Meirawan, Deddy (STKIP Yapis Dompu, 2022)
The purpose of this study is to determine the types of implicatures and the function of implicatures used by teachers when interacting with students in the classroom during the learning process. The reason for this research is because it wants to provide sources of information or references regarding the types of implicatures and the functions of implicatures that are expected to be useful for the institution where the researcher conducts the study, for teachers, for other students, other researchers or readers. This study used descriptive qualitative method. There are two videos that are used as a source of research data. The videos show the activities of the learning process in the classroom and the interactions between teachers and students. Collecting research data, the researcher transcribes the videos accurately in written form, and then classifies the transcription data based on the types of implicatures and implicature functions so that the data can be easily identified and analyzed. After all the data has been collected, the researcher analyzes the data and draws conclusions. The results of this study indicate that: (1) There are 13 types of implicatures and there are 96 implicature functions used by teachers in the videos used as research data. Implicature types are divided into 2 conventional types and 11 unconventional types. Meanwhile, the implicature functions are divided into 36 assertive functions, 29 directive functions, 28 expressive functions, and 3 commissive functions.